The right to freedom of expression and freedom of peaceful assembly in the context of human rights juris-diction of the European Court - Базов, Олександр (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Each restrictions on freedom of free expressions should be necessary in the democratic society. According to the European Court of Human Rights, the adjective «necessary» implies a «pressing social need». While doing its supervisory powers, the ECtHR assesses proportionality of restrictions, which are applied to the freedom of expression, according to the goal, which is seeking to achieve. Any disproportionate intervention, that was carried out to achieve a legitimate objective, will not be considered as «necessary in a democratic society» and would constitute a violation of Article 10 of the Convention. The limits of acceptable criticism are wider on some categories of persons and narrow in proportion to the reduction publicity of the person. Analysis of the Constitution of Ukraine and the ECHR shows that the Convention provides more grounds for restricting freedom of assembly than the Constitution of Ukraine, in particular the restriction of the right to protect the morals of others. In this regard, we believe that these grounds, including the protection of health or morals or the protection of the rights and freedoms of others, take precedence over the right to freedom of peaceful assembly. That human rights and freedoms, which are grounds for restricting the right to freedom of peaceful assembly protected by the Constitution of Ukraine and the Convention for the Protection of Human Rights and Fundamental Freedoms and are above the rights to freedom of peaceful assembly. It should be noted, that in Ukraine one of the causes of negative practice in jurisprudence, which was satisfied by claims to restrict the right to peaceful assembly only if there is a formal reason for it, is some unregulated issues of right realization to peaceful assembly by relevant national law.